A Chaos-Based Encryption Scheme for DCT Precoded OFDM-Based Visible Light Communication Systems - Zhongpeng Wang; Shoufa Chen (Journal of Electrical and Computer Engineering)
This paper proposes a physical encryption scheme for discrete cosine transform (DCT) precoded OFDM-based visible light communication systems by employing chaos scrambling. In the proposed encryption scheme, the Logistic map is adopted for the chaos mapping. The chaos scrambling strategy can allocate the two scrambling sequences to the real (I) and imaginary (Q) parts of OFDM frames according to the initial condition, which enhance the confidentiality of the physical layer. The simulation experimental results prove the efficiency of the proposed encryption method for DCT precoded OFDM-based VLC systems. The experimental results show that the proposed security scheme can protect the DCT precoded OFDM-based VLC from eavesdropper, while keeping the advantage of the DCT precoding technique, which can reduce the PAPR and improve the BER performance of OFDM-based VLC.